2017
DOI: 10.1039/c7mh00166e
|View full text |Cite
|
Sign up to set email alerts
|

Materials and toxicological approaches to study metal and metal-oxide nanoparticles in the model organism Caenorhabditis elegans

Abstract: Understanding the in vivo fate and transport of nanoparticles (NPs) is challenging, but critical. We review recent studies of metal and metal oxide NPs using the model organism Caenorhabditis elegans, summarizing major findings to date. In a joint transdisciplinary effort, we highlight underutilized opportunities offered by powerful techniques lying at the intersection of mechanistic toxicology and materials science,. To this end, we firstly summarize the influence of exposure conditions (media, duration, C. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…Over the past decades, it has been proved that C. elegans can be used as an animal model for studies on toxicity. , Considering these advantages including a short life cycle, a small size, good transparency, and a fully sequenced genome, C. elegans was often chosen as the priority model to elucidate the toxicity mechanism. , Previous studies demonstrated that C.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, it has been proved that C. elegans can be used as an animal model for studies on toxicity. , Considering these advantages including a short life cycle, a small size, good transparency, and a fully sequenced genome, C. elegans was often chosen as the priority model to elucidate the toxicity mechanism. , Previous studies demonstrated that C.…”
Section: Introductionmentioning
confidence: 99%
“…The different exposure media for C. elegans are either liquid or solid (Gonzalez‐Moragas et al 2017). The stability and uniformity of NPs should be maintained as much as possible, to ensure repeatability of the experiment.…”
Section: Exposure Of C Elegans To Nmsmentioning
confidence: 99%
“…It is an ideal model animal for studying neurobiology and developmental biology (Brenner 1974). To date, nanotoxicological studies using C. elegans have shown that exposure to particular concentrations of certain NPs causes multiple adverse effects in different systems of C. elegans through different toxicity pathways (Gonzalez‐Moragas et al 2017). Thus C. elegans has become a widely used biological model for assessing the toxicity of nanotechnology products and their potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents do not accurately mimic human physiology and pathophysiology in terms of exposure, injury and clearance of nanoparticles. In that aspect a gradual swift to well characterized relevant human in vitro models, invertebrate animal models and in silico simulations will be needed to limit the use of high numbers of animals and to produce large volume of data needed (Braakhuis et al, 2015 ; Clippinger et al, 2016 ; Polk et al, 2016 ; Sharma et al, 2016 ; Chen et al, 2017 ; Gonzalez-Moragas et al, 2017 ).…”
Section: Gaps Obstacles and Perspectives In The Field Of Pathophysiomentioning
confidence: 99%